Arctic National Wildlife Refuge : hearings before the Subcommittee on Fisheries and Wildlife Conservation and the Environment of the Committee on Merchant Marine and Fisheries, House of Representatives, One Hundred Second Congress, first session, on consideration of several proposals to authorize oil and gas leasing within the Arctic National Wildlife Refuge. - United States. Congress. House. Committee on Merchant Marine and Fisheries. Subcommittee on Fisheries and Wildlife Conservation and the Environment. (Washington : U.S. G.P.O. : For sale by the U.S. G.P.O., Supt. of Docs., Congressional Sales Office, 1991)
"Serial no. 102-35"--Pt.2 "Serial no. 102-26"--Pt. 1. "May 1, 1991; June 11, 1991; and July 16, 1991"--Pt. 1. Shipping list no.: 91-714-P (pt. 1). Distributed to some depository libraries in microfiche. Includes bibliographical references. Mode of access: Internet.